(untitled) (Environment & Health, 2020)
Objective: We analyzed the effectiveness of the barrier function of current technologies for the preparation of drinking water from the Dnister River and its tributaries, assessed its quality for compliance with sanitary requirements and evaluated the current schemes of water treatment and the quality of drinking water obtained from underground sources for centralized drinking water supply to the population in the Western region of Ukraine. Methods: We applied methods of analysis, hygienic monitoring, synthesis, generalization and bibliographic, comparative, descriptive ones. Results and conclusions: The water supply of the oblast centers of the western region of Ukraine was established to carry out at the expense of both surface water (Chernivtsi and Ivano-Frankivsk) and underground sources (Lviv and Ternopil). Unlike river sources, in the pipelines from the underground sources, the complex multi-stage water treatment technologies are not used because this water is much cleaner than surface water (maximum it is chlorination due to the long distances of water transport from the source to the consumer). For the production of drinking water from surface sources the traditional technological schemes are used, they consist of the following stages: water intake → reagent treatment of river water with flocculant and coagulant → settling and filtration through a quick filter → disinfection → clean water tank → water-supply system. Although, according to the expert opinions that water treatment of surface water requires more modern methods, drinking water is taken from the Dnister River or its tributaries in the Western region of Ukraine. This water is now estimated as clean or slightly contaminated for most indicators. As a result of performed measures, the population receives water, which, according to its indicators, complies with the State Sanitary Regulations and Standards 2.2.4-171-10 "Hygienic Requirements for Drinking Water Intended for Human Consumption". Considering that the main river-bed receives the pollution from the tributaries and the catchment area, it can be contended that the quality of surface water depends on the ecological state of the Dnister River basin and the degree of its pollution.